Distinct Roles of Classical and Lectin Pathways of Complement in Preeclamptic Placentae - Belmonte, Beatrice; Mangogna, Alessandro; Gulino, Alessandro; Cancila, Valeria; Morello, Gaia; Agostinis, Chiara; Bulla, Roberta; Ricci, Giuseppe; Fraggetta, Filippo; Botto, Marina; Garred, Peter; Tedesco, Francesco (Frontiers in Immunology, 2022)
Pre-eclampsia is a pregnancy complication characterized by defective vascular remodeling in maternal decidua responsible for reduced blood flow leading to functional and structural alterations in the placenta. We have investigated the contribution of the complement system to decidual vascular changes and showed that trophoblasts surrounding unremodeled vessels prevalent in preeclamptic decidua fail to express C1q that are clearly detected in cells around remodeled vessels predominant in control placenta. The critical role of C1q is supported by the finding that decidual trophoblasts of female C1qa-/- pregnant mice mated to C1qa+/+ male mice surrounding remodeled vessels express C1q of paternal origin. Unlike C1qa-/- pregnant mice, heterozygous C1qa+/- and wild type pregnant mice share a high percentage of remodeled vessels. C1q was also found in decidual vessels and stroma of normal placentae and the staining was stronger in preeclamptic placentae. Failure to detect placental deposition of C1r and C1s associated with C1q rules out complement activation through the classical pathway. Conversely, the intense staining of decidual endothelial cells and villous trophoblast for ficolin-3, MASP-1 and MASP-2 supports the activation of the lectin pathway that proceeds with the cleavage of C4 and C3 and the assembly of the terminal complex. These data extend to humans our previous findings of complement activation through the lectin pathway in an animal model of pre-eclampsia and provide evidence for an important contribution of C1q in decidual vascular remodeling.